2004
DOI: 10.1097/00129492-200407000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Intratympanic Gentamicin Therapy for Ménière’s Disease: A Meta-analysis

Abstract: The titration method of gentamicin delivery demonstrated significantly better complete (81.7%, p = 0.001) and effective (96.3%, p < 0.05) vertigo control compared with other methods. The low-dose method of delivery demonstrated significantly worse complete vertigo control (66.7%, p < 0.001) and trends toward worse effective vertigo control (86.8%, p = 0.05) compared with other methods. The weekly method of delivery trends toward less overall hearing loss (13.1%, p = 0.08), and the multiple daily method demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
146
2
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(160 citation statements)
references
References 21 publications
9
146
2
3
Order By: Relevance
“…The success of IT gentamicin has been examined in a number of series and summarized in several meta-analyses (1)(2)(3). Although vertigo control is achieved in more than 85% of the subjects in these series, hearing loss and posttreatment disequilibrium remain significant concerns.…”
mentioning
confidence: 99%
“…The success of IT gentamicin has been examined in a number of series and summarized in several meta-analyses (1)(2)(3). Although vertigo control is achieved in more than 85% of the subjects in these series, hearing loss and posttreatment disequilibrium remain significant concerns.…”
mentioning
confidence: 99%
“…High rates of complete or substantial vertigo control (over 85%) are achieved in many studies concerning ITG treatments [11][12][13] . Ototoxicity, which was a threat with former treatments using higher doses and titration protocols, can still be encountered rarely due to the cumulative effect of gentamicin [1] , thus hindering its common use. Moreover, it has been shown that even a single dose of gentamicin may cause ototoxicity in some cases as a result of idiosyncrasy [14] .…”
Section: Discussionmentioning
confidence: 99%
“…In a recent meta-analysis on ITG injection protocols, Chia et al [1] reported that weekly gentamicin injection protocols led to a mild ototoxicity rate compared to other protocols; but even in that case, the incidence of ototoxicity was as high as 13.1%. However, severe ototoxicity up to 34.7% was reported with daily multiple injection protocols [1] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations